Distribution of overwintering Calanus in the North Norwegian Sea. - Edvardsen, A.; Slagstad, D.; Semenova, T.; Pedersen, J.M.; Timonin, A. (European Geosciences Union, 2006)
During winter 2003 and 2004, zooplankton and hydrographic data were collected in the northern parts of the Norwegian Sea (68–72º N, 8–17º E) west of the Norwegian shelf break at depths down to 1800 m. The results cover both inter and intra annual changes of hydrography and distribution of Calanus spp. For the whole survey area, average seawater temperature down to 1000mwas higher in 2004 than in the same period in 2003. For the upper 500m the difference was ca. 1º C. Calanus finmarchicus dominated at ca. 75% of the total copepod abundance. Typical abundance of C. finmarchicus in the survey area was 30 000–40 000m-2. C. hyperboreus was found deeper than C. finmarchicus while other copepods were found at the depth of C. finmarchicus or shallower. From January to February 2004, the peak of abundance of C. finmarchicus and C. hyperboreus shifted approximately 300m upwards indicating that ascent from overwintering depth took place at a speed of 10md-1 during this period. In general, high abundance of copepods was found adjacent to the shelf slope while oceanic areas had low and intermediate abundance. In the southern part of the survey area, location of high and low copepod abundance shifted both between and within years. In the northern part of the survey area where the shelf slope is less steep, copepods was present at intermediate and high abundance during all surveys.